Faktor yang Mempengaruhi Tingkat Permintaan Ikan Mungkus (Sicyopterus Cynocephalus) di Rumah Makan Pinggiran Jalan Air Manna Kabupaten Bengkulu Selatan - Zendy Hd Sagita; Herri Fariadi; Rika Dwi Yulihartika (Jurnal Multidisiplin Dehasen (MUDE), 2026)
South Bengkulu Regency is well-known as a producer of mungkus fish (Sicyopterus cynocephalus). This has led to an increase in mungkus fish processing businesses, one of which is a restaurant located along Air Manna Road in South Bengkulu Regency, where mungkus fish is the main menu item. The objective of this study is to analyze the factors influencing the demand for mungkus fish (Sicyopterus cynocephalus) at the restaurant along Air Manna Road in South Bengkulu Regency. The research method employed a quantitative descriptive approach combined with multiple linear regression analysis. The results of the study indicate that the factors influencing the demand for mungkus fish are: the price of mungkus fish (X1), business owner income (X2), the quality of mungkus fish (X4), and weather (X5), while the price of tilapia (X3) does not influence the demand for mungkus fish at the roadside restaurant on Air Manna Road in South Bengkulu Regency.